PEMBERDAYAAN KELOMPOK PERAWATAN DIRI KUSTA (KPD) PUSKESMAS SLAHUNG DALAM PENGEMBANGAN POTENSI PEMBIBITAN TANAMAN BUAH - HAMAWI, MAHMUDAH; LAILA, ALFU; ETICA, USE; CAHYANTI, LUTFY DITYA (Jurnal Terapan Abdimas, 2017)
AbstractThe purpose of community service activities with the title Empowerment Group Care (KPD) Leprosy at public healthy Service, District Slahung by potential development fruit nursery, first objective are, to helping public healthy Service, District Slahung as the chief of activities KPD leprosy to increasing the participation rate of leprosy patients in KPD to attend the activities KPD by providing activities pull through the empowerment of leprosy patients in agriculture, especially fruit nurseries. The second objective is to increase the potential of agriculture in the district Slahung especially fruit by empowering KPD Leprosy public healthy Service, District Slahung. To achieve the goals of community service which have conducted the faculty team Agroteknologi Gontor Darussalam University, community service activities carried out in the form of materials, discussion and question and answer, simulation and practice. Once completed community service activities, there was an evaluation. Community service activities are carried out in public healthy Service, District Slahung can be concluded that an increase in the participation of members KPD KPD Leprosy activities. KPD members Leprosy quite interested in community service activities in the field of fruit plant nurseries because most members of the KPD Leprosy is a farmer. The KPD members of both leprosy have been able to carry fruit plant nurseries by grafting and cuttings. Abstrak Tujuan dari kegiatan pengabdian masyarakat dengan judul Pemberdayaan Kelompok Perawatan Diri (KPD) Kusta Puskesmas Slahung Dalam Pengembangan Potensi Pembibitan Tanaman Buah yang pertama adalah membantu puskesmas selaku pelaksana kegiatan KPD kusta dalam meningkatkan angka partisipasi penderita kusta di KPD untuk hadir di kegiatan KPD dengan memberikan kegiatan yang menarik melalui pemberdayaan penderita kusta di bidang pertanian khususnya pembibitan tanaman buah. Tujuan yang kedua adalah meningkatkan potensi pertanian di kecamatan Slahung khususnya tanaman buah dengan memberdayakan kelompok KPD Kusta Puskesmas Slahung. Untuk mencapai tujuan pengabdian masyarakat yang telah dilaksanakan tim dosen Agroteknologi Universitas Darussalam Gontor, kegiatan pengabdian kepada masyarakat dilakukan dalam bentuk pemberian materi, diskusi dan tanya jawab, simulasi serta praktek. Setelah kegiatan pengabdian masyarakat selesai, dilakukan evaluasi. Dari kegiatan pengabdian masyarakat yang dilaksanakan di Puskesmas Slahung di Kecamatan Slahung Kabupaten Ponorogo ini dapat disimpulkan bahwa terjadi peningkatan partisipasi anggota KPD pada kegiatan KPD Kusta. Anggota KPD Kusta cukup tertarik pada kegiatan pengabdian masyarakat dibidang pembibitan tanaman buah karena sebagian besar anggota KPD Kusta adalah petani. Para naggota KPD kusta sudah mampu melaksanakan pembibitan tanaman buah dengan okulasi dan stek.